VERBALIZATION OF THE CONCEPT OF YOUTH IN DIFFERENT LANGUAGES (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
This article analyzes the verbalization of the concept of "youth" in different languages based on cognitive linguistics and semantic theories. Fillmore's "Frame Semantics" approach, Lakoff and Johnson's metaphor theory, and Wierzbicka's semantic universals are used as methodological foundations for studying this concept. The article highlights the interpretation of this concept, along with its semantic and cognitive characteristics, using examples from various languages.